Com a palavra, o aluno: processos de retextualização na exposição oral acadêmica - Ana Virginia Lima da Silva (2013)
In this thesis, we focus on the processes of retextualization on oral academic exposure, aiming to highlight the possibilities of constitution of this genre and to contribute to the debate on what allows and/or raises difficulties for its production. The theoretical assumptions are basedon the socio-communicative model by Dolz, Noverraz and Schneuwly (2004 [1998]), on the retextualization works by Marcuschi (2001) and by Dell'Isola (2007), on the discussion about the relationships between orality and literacy studied by Marcuschi (2001), on the notion oftextual competence developed by Coutinho (2003), on the perspective of Textual Linguistics, and on the studies of Swales (1990) and Askehave and Swales (2001) about the discursive sphere, according to the North-American socio-rhetoric studies. The corpus of this researchconsists of oral presentations produced by undergraduate students in different courses; when analyzed, they led us to the conclusion that, in general, these students have difficulties in adjusting to the structural and linguistic prototypical characteristics of the oral exposuregenre. A comparison between the macrostructure of the source texts and of the retextualization strategies mobilized in electronic slides (support texts) shows us that, not always, the retextualized content corresponds to what is suggested in the source texts. From the analysis of ways to retextualize the source texts for oral exposures, we find that thecontent displayed is also contradictory to these texts. Thus, problems about understanding the theoretical basis used and about the mastery of the processes of retextualization significantly interfere in the quality of oral academic exposures, revealing the need for a teaching-learningprocess that allows students to develop the competence to appropriately expose academic texts.